(untitled) (Research, Society and Development, 2020)
In view of the consumer search for products with high nutritional value and practical consumption, present research aimed to develop a mixed juice of fruits and vegetables (liquid and powder). The method used was that of drying in foam mat. For the formation of foam, gum arabic and emulsifier were added to the mixed juice, afterwards the mixture was stirred in a mixer and carried to the tray dryer with air circulation and temperature of 60 °C. The liquid juice and its respective powder were analyzed for water content, total soluble solids, pH, total titratable acidity, reducing sugars and non-reducing sugars, ascorbic acid content (L *, a* and b*), ash, chlorides and fibers. A powdered juice with good physical and chemical characteristics was obtained, but it is salutary that complementary studies should be carried out, as reductions in green color and vitamin C content were observed after drying the juice in a foam layer.